Does Character Education Influence Student Discipline in Aqidah Akhlak Learning? Case Study at Madrasah Tsanawiyah Darussalam, Bogor City - Toyyibudin; Tamam, Abas Mansur; Supraha, Wido (Journal of Psychology and Sustainable Education, 2025)
Character education plays an important role in shaping the personality of students who are disciplined and responsible. This study aims to analyze the implementation of strengthening disciplinary character education and its implications for student discipline in Aqidah Akhlak learning at MTs. Darussalam, Bogor City. This study uses a quantitative approach with a correlational method to test the relationship between character education and student discipline. Data were collected through questionnaires given to 95 respondents selected using stratified random sampling techniques. Descriptive statistical analysis shows that the level of strengthening disciplinary character education is moderate, with an average value of 66.51. In contrast, the level of student discipline is high, with an average value of 75.73. The results of the Pearson correlation analysis show a significant positive relationship between strengthening character education and student discipline (r = 0.509, p <0.05). This indicates that the stronger the character education applied, the higher the level of student discipline. Therefore, strengthening character education must be optimized with a more systematic and participatory approach to improve student discipline in Aqidah Akhlak.